Pengaruh Sikap Berwirausaha, Kelompok Referensi, dan Keyakinan Diri terhadap Niat Berwirausaha (Studi pada Mahasiswa Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa) - Putri, Irma Vaulina; Subiyanto, Didik; Septyarini, Epsilandri (Journal of Economics, Bussiness and Management Issues, 2025)
This study aims to analyze the influence of entrepreneurial attitude, reference groups, and self-confidence on entrepreneurial intention among students of the Faculty of Economics at Sarjanawiyata Tamansiswa University. Employing a descriptive quantitative approach, the research involved 83 active students selected through purposive sampling. Data were analyzed using data quality tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results indicate that, partially, entrepreneurial attitude and self-confidence have a positive and significant effect on students’ entrepreneurial intention. In contrast, reference groups show a positive but not significant effect, suggesting that social support does not necessarily play a decisive role in shaping entrepreneurial intention. However, when analyzed simultaneously, all three variables have a significant influence on entrepreneurial intention. These findings highlight the importance of fostering positive attitudes and self-confidence through entrepreneurial training, networking, and experiential learning. The study recommends integrating entrepreneurial content into the curriculum, extending internship periods, providing entrepreneurship briefing forums, and developing campus business incubators. Future research is encouraged to focus on more specific educational settings, such as religious-based universities, and consider replacing the reference group variable with other more relevant factors.